Resilience improvement of an isotactic polypropylene-g-maleic anhydride by crosslinking using polyether triamine agents. (28th September 2019) - Létoffé, Adrien; Hoppe, Sandrine; Lainé, Richard; Canilho, Nadia; Pasc, Andreea; Rouxel, Didier; Jiménez Riobóo, Rafael J.; Hupont, Sébastien; Royaud, Isabelle; Ponçot, Marc
Abstract: The elaboration of new hybrid polymer/metal composite materials depends on the development of innovative polymer matrices with improved mechanical properties and high effective adhesion behaviour with metal surfaces. This way, a new type of polyolefin was developed based on a peculiar crosslinking reaction. For this elaboration, an iPP- g -MAH with 1 wt% of MAH was crosslinked with polyether triamine molecules by twin screw reactive extrusion. The evolution of the crosslinking reaction, the microstructure and the mechanical behaviour of the different materials were studied as a function of the NH2 :MAH molar ratio in the range of 0:1 and 1.5:1. Gel content determination and FTIR analysis were performed to characterise the material at the molecular scale, when differential scanning calorimetry, wide angle X-rays scattering and self-successive auto-nucleation techniques were used for a deep microstructure analysis. Brillouin spectroscopy showed an interesting evolution of the elastic constants at the microscopic scale and results were in good agreement with those obtained at the macroscopic scale by a video-controlled uniaxial tensile test. Moreover, it was demonstrated that the true mechanical behaviours switch from brittle to ductile illustrating an important improvement of the resilience ability of the synthetized materials as a function of the NH2 :MAH molar ratio even for molar ratio other than an equimolar ratio, with remaining MAH or NH2 chemical groups for further chemical reaction. Graphical abstract: From the 0.66:1 NH2 /MAH molar ratio, crosslinking enables maleated isotactic polypropylene to get higher mechanical resilience while keeping its functional property with available free MAH or NH2 grafts, confirmed by the FTIR analysis.Image 10414686 Highlights: A capped-end triblock polyethertriamine is used as a linker of an iPP- g -MAH 1 wt% by twin-screw reactive extrusion. The three-dimensional networks are characterized by FTIR and by the determination of gel content. The semi-crystalline microstructure is thermally described applying the Self-Successive Auto nucleation technique. A switch from brittle to ductile mechanical properties is observed studying the intrinsic true mechanical behaviours. Chemical functionality of matrices is maintained after crosslinking.